Official ERS technical standard: Global Lung Function Initiative reference values for static lung volumes in individuals of European ancestry. Issue 3 (11th March 2021) - Hall, Graham L.; Filipow, Nicole; Ruppel, Gregg; Okitika, Tolu; Thompson, Bruce; Kirkby, Jane; Steenbruggen, Irene; Cooper, Brendan G.; Stanojevic, Sanja; ,
Background: Measurement of lung volumes across the life course is critical to the diagnosis and management of lung disease. The aim of the study was to use the Global Lung Function Initiative methodology to develop all-age multi-ethnic reference equations for lung volume indices determined using body plethysmography and gas dilution techniques. Methods: Static lung volume data from body plethysmography and gas dilution techniques from individual, healthy participants were collated. Reference equations were derived using the LMS (lambda-mu-sigma) method and the generalised additive models of location shape and scale programme in R. The impact of measurement technique, equipment type and being overweight or obese on the derived lung volume reference ranges was assessed. Results: Data from 17 centres were submitted and reference equations were derived from 7190 observations from participants of European ancestry between the ages of 5 and 80 years. Data from non-European ancestry populations were insufficient to develop multi-ethnic equations. Measurements of functional residual capacity (FRC) collected using plethysmography and dilution techniques showed physiologically insignificant differences and were combined. Sex-specific reference equations including height and age were developed for total lung capacity (TLC), FRC, residual volume (RV), inspiratory capacity, vital capacity, expiratory reserve volume and RV/TLC. The derived equations were similar to previously published equations for FRC and TLC, with closer agreement during childhood and adolescence than in adulthood. Conclusions: Global Lung Function Initiative reference equations for lung volumes provide a generalisable standard for reporting and interpretation of lung volumes measurements in individuals of European ancestry. The GLI Network has developed all-ages reference equations for lung volumes for populations of European ancestry. The unification of GLI lung function reference equations will improve the interpretation of lung function in patients with lung disease. https://bit.ly/3hHZR1N